A’Pamps Enterprise / Aiman Fitri Nor Abdillah ... [et al.] - Nor Abdillah, Aiman Fitri; Muhammad Fauzi, Muhammad Syahir; Rishahfaizal, Mohamad Ikmal; Mohd Mothair, Muhammad Daneesh Zharfan (2021)
A’Pamps will be a food business specialized in offering traditional snack which is “apam balik” for various background of customer in this millennial era. We will focus on how to serve the best value of money and highest quality product to the customers. The food industry has improved a lot recently especially after the existence of social media. Based on our research, customer love to share photo on their social media and foods are included. Otherwise, customer love to find local and simple foods with a flash of a modern signature vision. With that in our mind, we decided to specialize and recreated our traditional food with new flavours so people from any age and background can enjoy it. Our stall will be open in a very famous tourism spot in Malaysia which is Genting Highlands. The idea to sell traditional food in the location because there are no others vendor sell the same criteria of food like us so it will be an advantage for A’Pamps. This distinguishes A’pamps from other shops in the eyes of customers and encourages them as well to try something new and unique. Thus, this will make A’pamps a premier shop to get interesting local food. This business requires RM110,000 as the start-up funding and total cash funding by the members of A’Pamps Enterprise is RM50,000. The business also applied for a loan for a total of RM60,000 so it will complete the start-up financing. The start-up funds will be utilized to cover the general and administrative cost of operation. The business expected to generate positive net earnings in the sixth months of the first year of operation. A’Pamps registered with the Suruhanjaya Syarikat Malaysia (SSM)on the date 16th December 2021.The business registered with the name of A’Pamps Enterprise and it is a partnerships business with a total of 4 members. Each of the partner holding position such as General Manager, Marketing Manager, Financial Manager and Operation Manager. Last but not least, since the forming of A’Pamps Enterprise, we have handled and listening to a lot of comments from the research. Before selling the products, we tried and error with all of the flavors and mostly, people love with the tester. We tried to produce and distributing the food to the community in Selangor and we received excellent feedback so we believe our plan to open A’Pamps in Genting Highland will be succeed